Psychological Impact of Corporate Social Responsibility Practices - Yapputro, Nikole Edmonda; Callista, Vania Cindy; Vercelli, Theresia Angela De; Sinamo, Maria Anastasya; Dewi, Fransisca Iriani R.; Suyasa, P. Tommy Y. S. (Journal of Ecohumanism, 2024)
There are various studies that have discussed the impact of Corporate Social Responsibility (CSR). However, the author has not found any studies that summarize this impact as a whole. The aim of this research is to summarize the various psychological impacts of CSR practices. CSR is a form of obligation carried out by company (managers) in carrying out activities based on community values ​​and expectations. This research uses the scoping review method. In the process of searching and selecting relevant literature, six databases were used, based on six inclusion criteria. A total of 95 articles published between 2014 and 2024 were identified, screened, tested for eligibility, and reviewed by the author. The author found at least 12 psychological impacts of CSR programs. The twelve psychological impacts are categorized based on benefits for the company, employees, and society. It is hoped that these various psychological impacts can become a basis for balancing companies in organizing, evaluating, and planning CSR practices.